Immigration and use of public spaces and food stores in a large city: A qualitative study on urban health inequalities - Jesús Rivera-Navarro; Elisa Brey; Manuel Franco (Elsevier, 2020)
The analysis of urban health transformations must include the study of how neighbourhoods are influenced by demographic changes such as immigration. The objective of this study was to analyse how the relationship between native and immigrant residents in neighbourhoods with different socio-economic levels influenced the use of urban health assets, such as public spaces and food stores. Three Madrid neighbourhoods of different socio-economic levels were selected and studied by conducting 37 semi-structured interviews and 29 focus groups. Data analysis was based on qualitative sequential discourse.The main finding was that the presence of immigrants in Madrid neighbourhoods, especially with low and medium socio-economic levels, was perceived negatively, affecting the use of public spaces and food stores. This negative perception unfolded in three dimensions: (1) difficulties for natives and immigrants to live together; (2) limitations on using public spaces caused by a feeling of insecurity; (3) criticism of immigrant food stores, especially Chinese-run food stores. Our findings showed a worrisome lack of social contact between immigrants and native residents, which affected the use of urban health assets, such as public spaces and food stores.